Comparison of intravenous tranexamic acid versus sublingual misoprostol in reducing blood loss in patients undergoing caesarean section-an analytical observational study - Deeksha Rao M.; M., Munikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preventing postpartum haemorrhage using uterotonics or other antifibrinolytic drugs is need of the hour among women undergoing caesarean section (CS). This study is to compare the effectiveness of intravenous Tranexamic acid versus sublingual misoprostol in reducing blood loss by assessing intraoperative and postoperative blood loss in patients undergoing CS. Methods: Analytical observational study was conducted in department of obstetrics and gynaecology at sri Devaraj URS medical college, among 118 pregnant women admitted for CS. Study was conducted between January 2020 to June 2021. The sample was divided equally into intravenous tranexamic acid and sublingual misoprostol groups. Number of mops, pads soaked, suction volume excluding the amniotic fluid, preoperative and post-operative haemoglobin, any complication were recorded. Results: The mean of mops counts in the misoprostol, TXA group were noted as 4.73±1.27, 3.2±1.45 respectively. Around 8.47% of the participants in the misoprostol group required uterotonics, whereas, 15.25% in the TXA group required uterotonics. The preoperative and postoperative haemoglobin in misoprostol group were identified as 11.67±1.37, 10.78±1.12 respectively, whereas it was identified as 11.76±1.43, 11.17±1.4 in TXA group. The common side effects identified in the misoprostol group was chills, vomiting and fever with 47.46%, 13.56% and 11.86% while, it was 11.86%, 5.08% and 3.39% in the TXA group. Conclusions: Both intravenous tranexamic acid, sublingual misoprostol could be prescribed as standard therapy to significantly control blood loss and increase the quality of surgery with better outcomes. But the use of TXA proved slightly better as there were lesser side effects and significantly lesser blood loss in uncomplicated cases.